(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Customer satisfaction is influenced by service quality, discipline and service innovation. There is a decrease in customer satisfaction, namely customers who are not happy because the service is long, the system is sometimes problematic, and the lack of information received by customers when making transactions is caused by the low quality of service, work discipline and service innovation at BNI Renon Branch employees. The formulation of the problem and the purpose of this study is to determine the effect of service quality, discipline and service innovation on customer satisfaction. This research was conducted at BNI Renon Branch as a population and 100 customers as a sample. Research data were collected using questionnaires, interviews, and observations. The collected data were then analyzed using validity tests, reliability tests, multiple linear regression tests, and the coefficient of determination. This study found that service quality, discipline, and service innovation positively and significantly influence customer satisfaction both simultaneously and partially. All independent variables in this study contribute 53.3% to customer satisfaction. Researchers suggest that BNI Renon Branch should provide training for employees so that later they have the ability to be able to handle transactions properly and always supervise employees while working, so that later employees always try to provide maximum service and provide a quick response when there are complaints from customers.